Working Together to Take Care of the Land: Building Bridges with Traditional Knowledge in the Gwich’in Settlement Area - Smith, Wynet (Ethnobotany Research and Applications, 2005)
Nits’òo nan k’atr’ahnahtyaa ts’àt nits’òo nan kak gwitr’it t’agwahàa’aa geenjit tr’iilee tr’igwähtsii gwizhit yeenoo dài’ nits’òo tr’igwiindài’ t’atr’ahdahch’aa geenjit ganiinji’tr’adhat. Gwitr’it geenjit tr’iilee tr’igwahtsii dài’ juk drin nits’òo gwiidandaii ts’àt yeenoo dài’ nits’òo tr’igwiindài’ gwit’atrahdahch’aa iisrits’àt geenjit gòo’aih. Canada gwizhit nan sridatr’igwijiinlik aii gwizhit juudin nan tr’ooheendal, nits’òo nan t’atrahdahch’aa ts’àt juudin nan gwits’àt k’agwahaadhat jii sridatr’igwijiinlik gwi’dinehtl’èe’ gwizhit geenjit gòo’aih. Gwich’in kaiik’it gwa’àn nits’òo nan k’atr’ahnyahtyaa geenjit tr’iilee tr’ałtsaii gwits’àt duuleh gwiinleii t’atràhdahch’aa. Jii dinehtł’eh gwizhit nits’òo nan k’atr’ahnyahtyaa ts’àt yeenoo dài’ nits’òo tr’igwiindài’ t’atr’ahdahch’aa giiniidhan geenjit gwidinithitł’oh. Gwiinzii gwitr’it gwìltsaii, gwiinzii gwitr’it gwìltsaii kwaa ts’àt nits’òo gwiinzii gwitr’it gwahahtsaa geenjit chan jii gwizhit gwidinithitł’oh. Gwitr’it t’agwäh’ii kat gat’igiiniidhan kwaa, nits’òo yeenjì’ gwa’àn uunjit kat gwitr’it t’agwäh’ii ts’àt kaiik’it gwa’àn gwizhit dinjii kat gat’igiiniidhan kwaa jii kat tthak gwits’agwighah t’iinch’uh. Nits’òo yeenoo dài’ gwitr’it geenjit tr’iilee gugwiłtsaii, kaiik’it gwizhit dinjii kat tthak gwizhit giheelyaa, jidii tthak gahgwiheedandaii geenjit dinehtł’eh kak nitr’ihee’aa aii geeghee yeenoo dài’ nits’òo tr’igwiindài’ gwinjik gwiinzii gwitr’it gwahahtsaa geenjit dinehtł’eh tr’ahahtsaa aii ts’àt kaiik’it gwizhit nits’òo gwiidandaii jii kat tthak gwinjik gwiinzii gwitr’it gwahähtsah. Gwitr’it gwahähtsaa geenjit tr’iilee tr’igwähtsii dài’ dinjii zhuh kat tthak gwizhit giheelyaa geenjit iisrits’àt gwijiinchii, jii gwik’iighè’ jidìi gahgidandaii, jidìi geenjit ganiinjì’gadhat ts’àt jidìi iisrits’àt guuveenjit gwijiinchii gwinjik gwiinzii gwitr’it gahahtsah. There is great interest in incorporating traditional knowledge into conservation and development planning. It is especially important to try to develop planning and management approaches that actually integrate traditional knowledge and western management systems. In northern Canada, modern comprehensive land claim agreements have been negotiated and signed with the intent of transferring lands, rights, and resource management responsibilities. Many important lessons can be derived from the integrated approach to conservation and resource planning undertaken in the Gwich’in Settlement Area. This paper outlines the key management structures and the systematic processes used to try and incorporate Gwich’in traditional knowledge. Successes and failures are highlighted and key strategies and tools are outlined as well. Key barriers included staff resistance, westernscience biases, and community concerns about westernapproaches. Key solutions were the use of culturally appropriate planning tools, full involvement of community groups, the setting of integrated, strategic research agendas, the development of traditional knowledge policies, and the development of other concrete mechanisms for incorporating local values and knowledge. It is necessary to have full involvement of the indigenous people in the design, development and implementation of the planning and management processes so that the entire system is more reflective of their knowledge, worldviews, and priorities.